1999
DOI: 10.1182/blood.v94.9.3067.421a32_3067_3076
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD10 by Human T Cells That Undergo Apoptosis Both In Vitro and In Vivo

Abstract: This study shows that human postthymic T cells express CD10 when undergoing apoptosis, irrespective of the signal responsible for initiating the apoptotic process. Cells from continuous T-cell lines did not normally express CD10, but became CD10+ when induced into apoptosis by human immunodeficiency virus (HIV) infection and exposure to CD95 monoclonal antibody, etoposide, or staurosporin. Inhibitors of caspases blocked apoptosis and CD10 expression. Both CD4+ and CD8+ T cells purified from normal peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…In lymphocytes, its expression is largely restricted to B‐cell compartments with a typically high rate of apoptosis (Chu et al, 2000). CD10 is not expressed by normal peripheral T cells or nodal peripheral T‐cell lymphomas, but is induced in T cells undergoing apoptosis during HIV infection in both in vivo and in vitro experiments (Cutrona et al , 1999). This close association with CD10 expression and apoptosis suggests that CD10 plays a role in the regulation of lymphocyte survival.…”
Section: Immunophenotypementioning
confidence: 99%
“…In lymphocytes, its expression is largely restricted to B‐cell compartments with a typically high rate of apoptosis (Chu et al, 2000). CD10 is not expressed by normal peripheral T cells or nodal peripheral T‐cell lymphomas, but is induced in T cells undergoing apoptosis during HIV infection in both in vivo and in vitro experiments (Cutrona et al , 1999). This close association with CD10 expression and apoptosis suggests that CD10 plays a role in the regulation of lymphocyte survival.…”
Section: Immunophenotypementioning
confidence: 99%
“…CD10 has also been shown to be present in a variety of neoplasms such as renal cell carcinoma, prostatic adenocarcinoma, transitional cell carcinoma, endometrial stromal sarcoma, pancreatic adenocarcinoma, rhabdomyosarcoma, malignant melanoma, schwannoma, endometrial stromal tumors, intraductal breast papilloma, ductal breast hyperplasia, breast fibroadenoma and phyllodes tumor (Xu et al, 2001(Xu et al, , 2002Moritani et al, 2002;Oliva et al, 2002). A possible role of CD10 in the identification and isolation of apoptosing T cells in vitro and ex vivo (Cutrona et al, 1999) and in the growth of androgen-independent prostate cancer has been suggested (Albrecht et al, 2002). CD10 has also been shown to play an important role in the progression of malignant melanoma (Bilalovic et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, these authors suggest that CD10 is capable to enhance cancer cells invasion and metastasis. A number of other studies also discuss CD10 regulating biological activities of peptide substanses by reducing the concentration for receptor binding and signal transduction (18,19,23). Having in mind these contradictory data, we believe that our results provide convinsing evidense at least for CD10 role in urothelial cancer invasiveness in underlying smooth muscle.…”
Section: Discussionmentioning
confidence: 62%